Physicochemical Characterization and Rheological Behavior Evaluation of the Liquid Crystalline Mesophases Developed with Different Silicones - Prestes, Paula Souza; Chorilli, Marlus [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Scarpa, Maria Virginia [UNESP]; Leonardi, Gislaine Ricci (Taylor & Francis Inc, 2010)
This article presented physicochemical characterization and rheological behavior evaluation of the liquid crystalline mesophases developed with different silicones. There were prepared 5 ternary systems, which were carried out the determination of the relative density, the electric conductivity and polarized light microscopy analysis, being selected two systems to promote the Preliminary Stability Tests. The results showed that System 1 obtained the major liquid crystal formation and a higher stability. The temperature influences in the systems stability and phases structure. In hot oven, observed oneself the mixture of lamellar and hexagonal phase, for both systems.
Keywords: Liquid crystal; phase diagrams; rheological behavior; silicones